CORN SILK OFFERS MULTIMECHANISTIC APPROACHES IN MITIGATING OBESITY IN RODENTS - Ahmed, Hanaa H; Hamza, Amal H; Kotob, Soheir E (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The current study aimed to investigate the effect of corn silk extracts (aqueous and methanolic) against obesity in an animal model. Methods: Animals were fed high-cholesterol diet (HCD) for 12 W to induce obesity and then treated either with Orlistat, corn silk extracts (aqueous and methanolic) for 6 W. Anthropometric measurements (abdominal circumference [AC], thoracic circumference [TC], and body mass index [BMI]) were recorded. Biochemical parameters including lipid profile (serum total cholesterol, triglycerides, low-density lipoprotein, high-density lipoprotein, and lipase), glucose, insulin, and homeostasis model assessment of basal insulin resistance were assayed. Inflammatory cytokines visfatin, haptoglobin (Hp), afamin, endothelin-1, calprotectin, and protein S100B levels were quantified. Results: Significant decrease in TC, AC, and BMI was detected in HCD-fed groups treated with corn silk extracts with respect to HCD-fed group. Biochemical analyses indicated marked hypolipidemic and hypoglycemic effects of corn silk extracts. Treatment of HCD-fed groups with corn silk extracts experienced significant regression of visfatin, Hp, endothelin-1, calprotectin, and protein S100B levels relative to HCD-fed group. Conclusion: In conclusion, the current findings revealed the antiobesity potential of corn silk extracts. This effect may be attributed to its hypolipidemic, hypoglycemic, and anti-inflammatory properties of the active phytochemicals present in the extracts. Keywords: Obesity, Corn silk, Insulin resistance, Hyperlipidemia, Inflammation, Rodents.